2015
DOI: 10.1038/srep11921
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Sub-10 nm Gate Oxide on MoS2 with Ultra Low Leakage and Enhanced Mobility

Abstract: The integration of ultra-thin gate oxide, especially at sub-10 nm region, is one of the principle problems in MoS2 based transistors. In this work, we demonstrate sub-10 nm uniform deposition of Al2O3 on MoS2 basal plane by applying ultra-low energy remote oxygen plasma pretreatment prior to atomic layer deposition. It is demonstrated that oxygen species in ultra-low energy plasma are physically adsorbed on MoS2 surfaces without making the flakes oxidized, and is capable of benefiting the mobility of MoS2 flak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 31 publications
5
80
1
Order By: Relevance
“…For the untextured surfaces, the peak at 225.78 eV in Fig. 14 (c [38], indicating that some MoS 2 remained on the surfaces as a result of deformation. This seems to be contrast to the Raman spectra in Fig.10b [39], suggesting some oxide components in the tribo-film are formed.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…For the untextured surfaces, the peak at 225.78 eV in Fig. 14 (c [38], indicating that some MoS 2 remained on the surfaces as a result of deformation. This seems to be contrast to the Raman spectra in Fig.10b [39], suggesting some oxide components in the tribo-film are formed.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…as well as nanometer scalability (to reduce their effective oxide thickness "EOT" for enhanced gate control over the MoS 2 channel). The interested reader is directed to various literature reports for further reading on these topics [317][318][319][320][321][322][323][324][325][326][327][328][329][330][331][332][333]. The focus of the following discussion is on the influence of dielectric engineering on important device parameters, such as doping, carrier mobility, ON-currents and contact resistance, and how dielectric engineering can be used to help enhance the performance of MoS 2 -based devices.…”
Section: Role Of Dielectrics In Doping and Mobility Engineeringmentioning
confidence: 99%
“…The electrical transport in TMD based FETs are significantly influenced by scattering sources including charge impurities, interfacial traps, and defects generated during the ALD process, leading to the degradation of electrical performance. Various technical efforts have been demonstrated to deposit homogeneous high-k dielectrics, such as the insertion of a seeding layer [85], remote plasma treatment [86], and ultraviolet-ozone exposure [87]. Liao et al [85] reported the deposition of Y 2 O 3 on MoS 2 as a buffer layer before the growth of HfO 2 dielectric.…”
Section: Basic Field Effect Transistorsmentioning
confidence: 99%